Nano plugging agent, preparation method thereof and drilling fluid system
By combining modified nanosilicon dioxide with hydrophobic polymers, a high-temperature and high-salt stable nanosealant was prepared, which solved the problem of insufficient performance of nanosealant in high-temperature and high-salt environments in the prior art. Effective sealing of micro-nano pore joints of hard brittle mud shale and stable improvement of well walls has been achieved.
Patent Information
- Application Number
- CN202410671958.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-02-07
AI Technical Summary
The nanosealing agents in existing drilling fluids have poor temperature and salt resistance in high-temperature and high-salt environments, making it difficult to effectively seal the micro-nano pores in hard brittle mud shale, resulting in instability of the well wall.
Modified nano-silicon dioxide as the main component, and the introduction of azobisisobutyronitrile, N,N-dimethacrylamide, methylallyl alcohol polyoxyethylene ether and alkyl methacrylate are prepared. A nanosealer with hydrophobicity and high temperature and high salt stability is produced.
The nanosealing agent still maintains excellent rheology performance, filtration loss performance and sealing performance under high temperature of 240°C and saturated salt environment, with a sealing rate of more than 90%, significantly improving the stability of the well wall.
Smart Images

Figure CN119391392A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of drilling technology, and in particular to a nano plugging agent, a preparation method thereof and a drilling fluid system. Background Art
[0002] With the development of unconventional oil and gas resources such as shale gas and tight oil, the instability of hard and brittle mud shale wellbore has become an urgent problem to be solved. The pore throat size of mud shale is generally between 5 and 50nm, and most hard and brittle mud shales have closed or open bedding and microcracks, and the capillary force is strong. Under the action of positive pressure difference and capillary pressure, drilling fluid is easy to invade, resulting in wellbore instability.
[0003] Conventional plugging agents for water-based drilling fluids are generally asphalt, ultrafine calcium carbonate, elastic graphite, etc., which are mainly micron-sized and difficult to effectively plug the micro-nano pores and cracks of mudstone. The key to maintaining the stability of shale wellbore is to use high-performance nano plugging agents to strengthen the sealing of micropores, microcracks and bedding structures. At present, the research on nano plugging agents mainly includes: inorganic nanoparticles, organic nanoparticles and inorganic / organic composite nanoparticles. Inorganic / organic composite nanoparticles combine the rigidity, dimensional stability and thermal stability of inorganic materials with the toughness and multiple action sites of polymers, becoming the development direction of nano plugging agents. Summary of the invention
[0004] In view of the shortcomings of existing plugging agents, which have insufficient resistance to ultra-high temperature and salt, this application proposes a nano plugging agent, a preparation method thereof and a drilling fluid system. This application adopts the following technical solutions:
[0005] In a first aspect, the present application discloses a nano plugging agent, the nano plugging agent comprising the following ingredients: modified nano silicon dioxide, azobisisobutyronitrile, N,N-dimethylacrylamide, methallyl alcohol polyoxyethylene ether and alkyl methacrylate;
[0006] Wherein, the addition amount of the azobisisobutyronitrile is 0.5-2% of the mass of the modified nano-silicon dioxide;
[0007] The mass ratio of the N,N-dimethylacrylamide to the modified nano-silicon dioxide is (1-2):2;
[0008] The mass ratio of the methyl allyl alcohol polyoxyethylene ether to the modified nano silicon dioxide is (2-3):2;
[0009] The mass ratio of the alkyl methacrylate to the modified nano-silica is (2-3):2.
[0010] Optionally, the components of the modified nano-silica include nano-silica and a silane coupling agent;
[0011] The mass ratio of the nano-silicon dioxide to the silane coupling agent is (3-5):1.
[0012] Optionally, the silane coupling agent is one or more of γ-methacryloxypropyltrimethoxysilane and 3-(isomethacryloxy)propyltrimethoxysilane.
[0013] Optionally, the alkyl methacrylate is one or more of isooctyl methacrylate, dodecyl methacrylate and octadecyl methacrylate.
[0014] Optionally, the particle size of the nano plugging agent is 20 to 300 nm.
[0015] In a second aspect, the present application discloses a method for preparing the nano plugging agent as described in the first aspect, the preparation method comprising:
[0016] Preparation of modified nano-silica;
[0017] Under a nitrogen atmosphere, dissolving the modified nano-silica into N,N-dimethylformamide to obtain a first dispersed system;
[0018] Adding azobisisobutyronitrile, N,N-dimethylacrylamide, methallyl alcohol polyoxyethylene ether and alkyl methacrylate to the first dispersed system to obtain a second dispersed system;
[0019] reacting the second dispersed system at 60-100° C.;
[0020] The second dispersed system after the reaction is separated, and the separated solid is washed with tetrahydrofuran and then dried to obtain a hydrophobic associating polymer modified nano plugging agent.
[0021] Optionally, the preparation of modified nano-silicon dioxide includes:
[0022] Add nano-silicon dioxide into the ethanol solution and disperse it evenly;
[0023] At a temperature of 60° C., continuously adding a silane coupling agent to the ethanol solution containing nano-silicon dioxide to carry out a modification reaction;
[0024] The modified reaction product is separated, and the separated solid is washed with anhydrous ethanol and then dried to obtain modified nano silicon dioxide.
[0025] In a third aspect, the present application discloses a drilling fluid system, wherein the drilling fluid system includes the nano plugging agent described in the first aspect.
[0026] Optionally, the drilling fluid system further comprises the following components: anti-salt soil, fluid loss reducer and sodium chloride.
[0027] Optionally, in the drilling fluid system, the mass percentage of the nano plugging agent is 2wt% to 3wt%.
[0028] In summary, the beneficial effects of the present application compared with the prior art include:
[0029] 1. The nano plugging agent in the embodiment of the present application is based on modified nano silica, and further introduces temperature and salt resistant monomers such as long hydrophobic chains and long chain ethoxy groups, and adjusts the monomer ratio so that the nano plugging agent has both rigid nano silica and flexible hydrophobic chains and polyethylene oxide chains. Nano silica can form a rigid support, and the polymer shell can be deformed to block pores of different shapes and sizes, thereby achieving a tight seal for micro-nano pores. It has been experimentally demonstrated that the nano plugging agent prepared by the present invention still has excellent rheological properties, filtration reduction properties and plugging properties after aging in a high temperature (240°C) high salt (saturated salt) environment.
[0030] 2. The nano plugging agent in the embodiment of the present application has a particle size between 20 and 300 nm, thereby effectively plugging a large number of micro-nano pores in hard and brittle shale.
[0031] 3. The nano plugging agent in the embodiment of the present application, by introducing a long-chain polyethylene glycol non-ionic structure into the polymer, can precipitate under high temperature conditions to form a plugging layer. Compared with commonly used micron-level plugging agents and unmodified nanomaterials, the plugging agent in the present application has a better plugging effect on micro-nano pores under high temperature conditions. After hot rolling at 240°C, the plugging rate of micro-nano pores is above 90%.
[0032] 4. The nano plugging agent in the embodiment of the present application has little effect on the rheological properties of the drilling fluid after being added to the drilling fluid, so that the plugging effect can be exerted without affecting the performance of the drilling fluid itself.
[0033] 5. The nano plugging agent in the embodiment of the present application can still stably play a plugging role in a drilling fluid system with a sodium chloride content of 15%, and has good salt resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the synthesis route of the nano plugging agent in the embodiment of the present application;
[0035] Figure 2 It is a transmission electron microscope image of the nano plugging agent in the embodiment of the present application. DETAILED DESCRIPTION
[0036] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0037] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims.
[0038] The inventors have found that the nano plugging agents commonly used in existing water-based drilling fluids have poor temperature and salt resistance and low plugging rate. To address the above problems, the inventors have proposed a nano plugging agent, a preparation method thereof and a drilling fluid system.
[0039] The present application is described in detail below through specific examples and comparative examples:
[0040] Example 1
[0041] The nano plugging agent in this embodiment includes the following components: nano silicon dioxide, γ-methacryloxypropyltrimethoxysilane, azobisisobutyronitrile, N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether (molecular weight 2400) and dodecyl methacrylate (DMA).
[0042] Among them, the mass ratio of nano silica and γ-methacryloxypropyltrimethoxysilane is 4:1, the mass of azobisisobutyronitrile is 2% of the mass of modified nano silica, and the mass ratio of modified nano silica, N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether and DMA is 2:1:2:2.
[0043] The nano plugging agent in this embodiment is prepared according to the following process:
[0044] (1) Preparation of modified nano-silica
[0045] Add 90mL of anhydrous ethanol and 10mL of distilled water to a 250mL three-necked flask, add 20g of nano-silica while stirring at a stirring speed of 300rpm, and stir for 20min after adding to make it evenly dispersed. Then continue to add 5g of γ-methacryloxypropyltrimethoxysilane to the three-necked flask at 60°C and react for 8 hours. After the reaction is completed, the reaction system is cooled to room temperature and centrifuged at a speed of 7500rpm. Finally, the separated solid is washed with anhydrous ethanol for more than 3 times and dried in an oven to obtain modified nano-silica.
[0046] (2) Preparation of hydrophobic associating polymer modified nano plugging agent
[0047] Under nitrogen atmosphere, 10 g of the modified nano-silica in (1) was dissolved in 100 mL of N, N-dimethylformamide, and then 0.2 g of azobisisobutyronitrile, 5 g of N, N-dimethylacrylamide, 10 g of methyl allyl alcohol polyoxyethylene ether and 10 g of DMA were added, and ultrasonic dispersion was performed for 30 min to obtain a dispersion system. The dispersion system was reacted at 80° C. for 8 hours at a stirring speed of 200 rpm. After the reaction, the dispersion system was cooled to room temperature and centrifuged at a speed of 7500 rpm. Finally, the separated solid was washed with tetrahydrofuran for 3 to 5 times and dried in an oven to obtain a hydrophobic associating polymer modified nano plugging agent.
[0048] In this embodiment, the synthesis route of the hydrophobic associating polymer modified nano plugging agent is as follows: Figure 1 As shown in the transmission electron microscopy image of the hydrophobic associating polymer modified nano plugging agent Figure 2 As shown, the particle size of the nano plugging agent is tested using a laser scattering instrument, and the particle size of the nano plugging agent is between 20 and 300 nm.
[0049] Example 2
[0050] The components of the plugging agent in this embodiment are the same as those in Example 1, except that, in this embodiment, the mass ratio of nano-silica to γ-methacryloxypropyltrimethoxysilane is 3:1, the mass of azobisisobutyronitrile is 1% of the mass of modified nano-silica, and the mass ratio of modified nano-silica, N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether and DMA is 2:2:3:3.
[0051] The plugging agent in this embodiment is prepared according to the following process:
[0052] (1) Preparation of modified nano-silica
[0053] Add 90mL of anhydrous ethanol and 10mL of distilled water to a 250mL three-necked flask, add 15g of nano-silica while stirring at a stirring speed of 300rpm, and stir for 20min after adding to make it evenly dispersed. Then continue to add 5g of γ-methacryloxypropyltrimethoxysilane to the three-necked flask at 60°C and carry out the modification reaction for 8 hours. After the reaction is completed, the reaction system is cooled to room temperature and centrifuged at a speed of 7500rpm. Finally, the separated solid is washed with anhydrous ethanol for more than 3 times and dried in an oven to obtain modified nano-silica.
[0054] (2) Preparation of hydrophobic associating polymer modified nano plugging agent
[0055] Under nitrogen atmosphere, 10 g of the modified nano-silica in (1) was dissolved in 100 mL of N, N-dimethylformamide, and then 0.1 g of azobisisobutyronitrile, 10 g of N, N-dimethylacrylamide, 15 g of methyl allyl alcohol polyoxyethylene ether (molecular weight 2400) and 15 g of DMA were added, and ultrasonic dispersion was performed for 30 min to obtain a dispersion system. The dispersion system was reacted at 80° C. for 8 hours at a stirring speed of 200 rpm. After the reaction was completed, the dispersion system was cooled to room temperature and centrifuged at a speed of 7500 rpm. Finally, the separated solid was washed with tetrahydrofuran for 3 to 5 times and dried in an oven to obtain a hydrophobic associating polymer modified nano plugging agent.
[0056] Example 3
[0057] The components of the plugging agent in this embodiment are the same as those in Example 1, except that, in this embodiment, the mass ratio of nano-silica to γ-methacryloxypropyltrimethoxysilane is 5:1, the mass of azobisisobutyronitrile is 0.5% of the mass of modified nano-silica, and the mass ratio of modified nano-silica, N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether and DMA is 2:1.5:2.5:2.5.
[0058] The plugging agent in this embodiment is prepared according to the following process:
[0059] (1) Preparation of modified nano-silica
[0060] Add 90mL of anhydrous ethanol and 10mL of distilled water to a 250mL three-necked flask, add 10g of nano-silica while stirring at a stirring speed of 300rpm, and stir for 20min after adding to make it evenly dispersed. Then continue to add 2g of γ-methacryloxypropyltrimethoxysilane to the three-necked flask at 60°C and react for 8 hours. After the reaction is completed, the reaction system is cooled to room temperature and centrifuged at a speed of 7500rpm. Finally, the separated solid is washed with anhydrous ethanol for more than 3 times and dried in an oven to obtain modified nano-silica.
[0061] (2) Preparation of hydrophobic associating polymer modified nano plugging agent
[0062] Under nitrogen atmosphere, 10 g of the modified nano-silica in (1) was dissolved in 100 mL of N, N-dimethylformamide, and then 0.05 g of azobisisobutyronitrile, 7.5 g of N, N-dimethylacrylamide, 12.5 g of methyl allyl alcohol polyoxyethylene ether (molecular weight 2400) and 12.5 g of DMA were added, and ultrasonic dispersion was performed for 30 min to obtain a dispersion system. The dispersion system was reacted at 80° C. for 8 hours at a stirring speed of 200 rpm. After the reaction was completed, the dispersion system was cooled to room temperature and centrifuged at a speed of 7500 rpm. Finally, the separated solid was washed with tetrahydrofuran for 3 to 5 times and dried in an oven to obtain a hydrophobic associating polymer modified nano plugging agent.
[0063] Example 4
[0064] The difference between this embodiment and embodiment 1 is that, in the components of the plugging agent of this embodiment, 3-(isomethacryloyloxy)propyltrimethoxysilane is used to replace γ-methacryloyloxypropyltrimethoxysilane.
[0065] Example 5
[0066] The difference between this embodiment and embodiment 1 is that, in the components of the plugging agent of this embodiment, isooctyl methacrylate (EHMA) is used instead of dodecyl methacrylate (DMA).
[0067] Example 6
[0068] The difference between this embodiment and embodiment 1 is that, in the components of the plugging agent of this embodiment, octadecyl methacrylate (SMA) is used instead of dodecyl methacrylate (DMA).
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that in the preparation process of modified nano-silica, the masses of nano-silica and γ-methacryloxypropyltrimethoxysilane are 20g and 5g respectively. In the preparation process of hydrophobic associating polymer modified nano plugging agent, the masses of each component are: modified nano-silica 10g, azobisisobutyronitrile 0.04g, N,N-dimethylacrylamide 4g, methyl allyl alcohol polyoxyethylene ether 8g, DMA8g. Other preparation processes are the same.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that in this comparative example, during the preparation of modified nano-silica, the masses of nano-silica and γ-methacryloxypropyltrimethoxysilane are 20 g and 5 g, respectively. During the preparation of the hydrophobic associating polymer modified nano-blocking agent, the masses of each component are: modified nano-silica 10 g, azobisisobutyronitrile 0.4 g, N,N-dimethylacrylamide 15 g, methyl allyl alcohol polyoxyethylene ether 20 g, DMA 20 g. The other preparation processes are the same.
[0073] Comparative Example 3
[0074] The difference between this comparative example and comparative example 1 is that, in the preparation process of the modified nano-silica, the masses of the nano-silica and γ-methacryloxypropyltrimethoxysilane are 20 g and 3 g, respectively.
[0075] Comparative Example 4
[0076] The difference between this comparative example and comparative example 2 is that, in the preparation process of the modified nano-silica, the masses of the nano-silica and γ-methacryloxypropyltrimethoxysilane are 20 g and 10 g, respectively.
[0077] Comparative Example 5
[0078] In this comparative example, the plugging agent was prepared according to the following process:
[0079] Add 90mL of anhydrous ethanol and 10mL of distilled water to a 250mL three-necked flask, add 20g of nano-silica while stirring at a stirring speed of 300rpm, and stir for 20min after adding to make it evenly dispersed. Then continue to add 5g of γ-methacryloxypropyltrimethoxysilane to the three-necked flask at 60°C and react for 8 hours. After the reaction is completed, the reaction system is cooled to room temperature and centrifuged at a speed of 7500rpm. Finally, the separated solid is washed with anhydrous ethanol for more than 3 times and dried in an oven to obtain modified nano-silica. The modified nano-silica is directly used as a plugging agent.
[0080] Comparative Example 6
[0081] In this comparative example, the plugging agent was prepared according to the following process:
[0082] In a nitrogen atmosphere, 5g of γ-methacryloxypropyltrimethoxysilane, 0.2g of azobisisobutyronitrile, 5g of N,N-dimethylacrylamide, 10g of methyl allyl alcohol polyoxyethylene ether (molecular weight 2400) and 10g of dodecyl methacrylate (DMA) were added to 100mL of N,N-dimethylformamide and ultrasonically dispersed for 30min. The above dispersion system was reacted at 80°C for 8 hours at a stirring speed of 200rpm. After the reaction, the system naturally cooled to room temperature and centrifuged at a speed of 7500rpm. The separated solid was washed with tetrahydrofuran for 3 to 5 times and dried in an oven to obtain a hydrophobically associating polymer. The hydrophobically associating polymer was directly used as a plugging agent.
[0083] Comparative Example 7
[0084] In this comparative example, the plugging agent is prepared by using unmodified nano-silicon dioxide, and the specific process is as follows:
[0085] Under nitrogen atmosphere, 10g of nano-silicon dioxide (average particle size of 20nm) was dissolved in 100mL of N,N-dimethylformamide, and then 0.2g of azobisisobutyronitrile, 5g of N,N-dimethylacrylamide, 10g of methyl allyl alcohol polyoxyethylene ether and 10g of DMA were added, and ultrasonic dispersion was performed for 30min to obtain a dispersion system. The dispersion system was reacted at 80°C for 8 hours at a stirring speed of 200rpm. After the reaction, the dispersion system was cooled to room temperature and centrifuged at a speed of 7500rpm. Finally, the separated solid was washed with tetrahydrofuran for 3 to 5 times and dried in an oven to obtain a plugging agent.
[0086] Comparative Example 8
[0087] In this comparative example, 2000 mesh ultrafine calcium carbonate was used as a plugging agent.
[0088] Comparative Example 9
[0089] In this comparative example, highly acid-soluble sulfonated asphalt was used as the plugging agent.
[0090] The contents of the components in Examples 1 to 3 and Comparative Examples 1 to 4 are shown in Table 1:
[0091] Table 1 Content of each component in Examples 1 to 3 and Comparative Examples 1 to 4
[0092]
[0093]
[0094] The plugging agents in the above examples and comparative examples were tested for rheological properties and evaluated for core plugging performance:
[0095] (i) Rheological properties test
[0096] Add 4% salt-resistant soil by mass into deionized water, stir at high speed for 20 minutes, and cure at 25°C for 24 hours to obtain drilling fluid base slurry. Add 2wt% of the plugging agents of the above embodiments and comparative examples to the drilling fluid base slurry, respectively, and refer to the test method in "GB / T 29170-2012 Laboratory Test of Drilling Fluids in Petroleum and Natural Gas Industry", respectively measure and calculate the apparent viscosity AV, plastic viscosity PV and dynamic shear force YP of the drilling fluid base slurry containing different plugging agents at room temperature and after aging for 16 hours at 240°C in a roller heating furnace. The drilling fluid base slurry without any plugging agent is used as a blank control group, and the experimental results are shown in Table 2:
[0097] Table 2 Apparent viscosity AV, plastic viscosity PV and dynamic shear force YP of each group of drilling fluid base slurry
[0098]
[0099]
[0100] As can be seen from Table 2, compared with the drilling fluid base slurry, after adding the plugging agent in Examples 1 to 6, the viscosity and shear force of the drilling fluid system are enhanced to a certain extent compared with the base slurry, but the increase in the viscosity of the system is small. After hot rolling at 240°C, the viscosity and dynamic shear force of the drilling fluid system in each embodiment and comparative example are reduced. After adding the plugging agent (Comparative Example 1) or modified nano-silicon dioxide (Comparative Example 5) prepared according to the formula of Comparative Example 1 and Comparative Example 3, the viscosity and shear force of the drilling fluid system do not change significantly. After adding the plugging agent or hydrophobic associating polymer (Comparative Example 6) prepared according to the formula of Comparative Example 2 and Comparative Example 4, the viscosity and shear force of the drilling fluid system are significantly increased, with obvious viscosity-enhancing and shear-enhancing effects, and the rheological properties of the drilling fluid system have significant changes. After adding unmodified nano-silicon dioxide (Comparative Example 7) and 2000 mesh ultrafine calcium carbonate (Comparative Example 8), the viscosity-enhancing and shear-enhancing effects are not obvious. After adding the highly acid-soluble sulfonated asphalt (Comparative Example 9), the viscosity and dynamic shear force of the drilling fluid base slurry increased after hot rolling, and the increase was greater than that of the plugging agents in Examples 1 to 6.
[0101] It can be further known from the above results that in the formulas of Examples 1 to 6, the mass of azobisisobutyronitrile is between 0.5% and 2% of the mass of modified nano-silica, the mass ratio of N,N-dimethylacrylamide to modified nano-silica is between (1 to 2):2, and the mass ratios of methyl allyl alcohol polyoxyethylene ether and alkyl methacrylate to modified nano-silica are respectively between (2 to 3):2. After adding it to the drilling fluid base slurry, the viscosity and shear force of the drilling fluid system are enhanced to a certain extent compared with the base slurry, but the increase in the viscosity of the system is small, indicating that the plugging agent in the present invention has little effect on the rheological properties of the base slurry, which is in line with the inventor's expectations. And this result is better than that in Comparative Examples 2 and 4, where the mass ratio of N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether, alkyl methacrylate and modified nano-silica is greater than 2:3:3:2.
[0102] (ii) Core sealing performance evaluation
[0103] The penetration rate was 10×10 -3 μm 2 The artificial core of about simulates the micro-nano porous formation. The preparation method of the water-based drilling fluid base slurry is as follows: add 4% of anti-salt soil by mass to deionized water, stir at high speed for 20 minutes, and cure at 25°C for 24 hours to obtain the drilling fluid base slurry. Under high-speed stirring conditions, 2% of the anti-ultra-high temperature filtration reducer CPJ (China Petroleum Engineering and Technology Research Institute Co., Ltd.), 3wt% of the plugging agent of the above embodiment and comparative example, and 15% of sodium chloride are added to the drilling fluid base slurry to obtain a drilling fluid system. Finally, the drilling fluid system is aged at 240°C for 16 hours. After cooling to room temperature, the permeability change of the artificial core before and after the intrusion of the drilling fluid system is measured, and the plugging rate of different plugging agents on the artificial core is calculated. The plugging rate calculation formula is (initial permeability-permeability after plugging) / initial permeability×100%. The experimental results are shown in Table 3:
[0104] Table 3 Experimental results of plugging rate of plugging agent on formation core
[0105]
[0106]
[0107]
[0108] As shown in Table 3, the plugging rate of the drilling fluid base slurry reaches 69%, which has a certain plugging ability. After adding the plugging agent in Examples 1 to 6 and hot rolling at 240°C, the plugging rate is significantly improved, and the plugging rate of the drilling fluid system is above 90%. After adding modified nano-silica, hydrophobic associating polymer, unmodified nano-silica, 2000 mesh ultrafine calcium carbonate and highly acid-soluble sulfonated asphalt, the plugging rate of the drilling fluid system is improved, but it is lower than the plugging rate of the plugging agent in Examples 1 to 6.
[0109] According to the above analysis, the plugging performance of the plugging agent prepared according to the set formula in Examples 1 to 6 is better than that in Comparative Example 1 when the mass ratio of each monomer to modified nano-silica is less than 1:2:2:2. When the mass ratio of each monomer to modified nano-silica in Comparative Example 2 is greater than 2:3:3:2, the corresponding plugging rate is reduced in comparison. Therefore, the inventors determined the addition amount of azobisisobutyronitrile to be 0.5-2% of the mass of modified nano-silica, and the mass ratio of N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether, alkyl methacrylate to modified nano-silica to be (1-2): (2-3): (2-3): 2. The plugging performance of the plugging agent within this ratio range meets the expected effect of the inventors.
[0110] In addition, the plugging performance of the plugging agent prepared according to the set formula in Examples 1 to 6 is better than that of the case where the mass ratio of nano-silica to silane coupling agent is less than 3:1 in Comparative Example 3, and is also better than that of the case where the mass ratio of nano-silica to silane coupling agent is greater than 5:1 in Comparative Example 4. Therefore, the inventors determined the mass ratio of nano-silica to silane coupling agent to be between (3 to 5):1.
[0111] From the above analysis, it can be further known that among Examples 1 to 6, Example 2 is further superior to the other examples. That is, when the mass ratio of the silane coupling agent to the nano-silica is 3:1, and the mass ratio of N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether, alkyl methacrylate to the modified nano-silica is 2:3:3:2, the plugging performance of the plugging agent is superior to that of the other examples.
[0112] The above description includes examples of one or more embodiments. Of course, it is impossible to describe all possible combinations of components or methods for the purpose of describing the above embodiments, but it should be recognized by those skilled in the art that the various embodiments may be further combined and arranged. Therefore, the embodiments described herein are intended to cover all such changes, modifications and variations that fall within the scope of protection of the appended claims. In addition, with respect to the term "comprising" used in the specification or claims, the word is covered in a manner similar to the term "including", as explained by "including" used as a transitional word in the claims. In addition, any term "or" used in the specification of the claims is intended to mean "non-exclusive or".
Claims
1. A nano plugging agent, characterized in that: The invention comprises the following ingredients: modified nano-silica, azobisisobutyronitrile, N,N-dimethylacrylamide, methyl allyl alcohol polyoxyethylene ether and alkyl methacrylate; Wherein, the mass of the azobisisobutyronitrile is 0.5-2% of the mass of the modified nano-silicon dioxide; The mass ratio of the N,N-dimethylacrylamide to the modified nano-silicon dioxide is (1-2):2; The mass ratio of the methyl allyl alcohol polyoxyethylene ether to the modified nano silicon dioxide is (2-3):2; The mass ratio of the alkyl methacrylate to the modified nano-silica is (2-3):
2.
2. The nano plugging agent according to claim 1, characterized in that: The components of the modified nano-silicon dioxide include nano-silicon dioxide and a silane coupling agent; The mass ratio of the nano-silicon dioxide to the silane coupling agent is (3-5):
1.
3. The nano plugging agent according to claim 2, characterized in that: The silane coupling agent is one or more of γ-methacryloxypropyltrimethoxysilane and 3-(isomethacryloxy)propyltrimethoxysilane.
4. The nano plugging agent according to claim 1, characterized in that: The alkyl methacrylate is one or more of isooctyl methacrylate, dodecyl methacrylate or octadecyl methacrylate.
5. The nano plugging agent according to claim 1, characterized in that: The particle size of the nano plugging agent is 20-300 nm.
6. The method for preparing the nano plugging agent according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Preparation of modified nano-silica; Under a nitrogen atmosphere, dissolving the modified nano-silica into N,N-dimethylformamide to obtain a first dispersed system; Adding azobisisobutyronitrile, N,N-dimethylacrylamide, methallyl alcohol polyoxyethylene ether and alkyl methacrylate to the first dispersed system to obtain a second dispersed system; reacting the second dispersed system at 60-100° C.; The second dispersed system after the reaction is separated, and the separated solid is washed with tetrahydrofuran and then dried to obtain a hydrophobic associating polymer modified nano plugging agent.
7. The preparation method according to claim 6, characterized in that: The preparation of modified nano silicon dioxide comprises: Add nano-silicon dioxide into the ethanol solution and disperse it evenly; At a temperature of 60° C., a silane coupling agent is continuously added to the ethanol solution containing nano-silicon dioxide to carry out a modification reaction; The modified reaction product is separated, and the separated solid is washed with anhydrous ethanol and then dried to obtain modified nano silicon dioxide.
8. A drilling fluid system, characterized in that: The drilling fluid system comprises the nano plugging agent according to any one of claims 1 to 5.
9. The drilling fluid system according to claim 8, characterized in that: The drilling fluid system also includes the following components: anti-salt soil, fluid loss reducer and sodium chloride.
10. The drilling fluid system according to claim 9, characterized in that: In the drilling fluid system, the mass percentage of the nano plugging agent is 2wt% to 3wt%.